Effects of high intensity exercise on isoelectric profiles and SDS-PAGE mobility of erythropoietin - Voss, S.; Lüdke, A.; Romberg, S.; Schänzer, E.; Flenker, U.; de Marees, M.; Achtzehn, S.; Mester, J.; Schänzer, W. (International Journal of Sports Medicine, 2010)
Exercise induced proteinuria is a common phenomenon in high performance sports. Based on the appearance of so called "effort urines" in routine doping analysis the purpose of this study was to investigate the influence of exercise induced proteinuria on IEF profiles and SDS-PAGE relative mobility values (rMVs) of endogenous human erythropoietin (EPO). Twenty healthy subjects performed cycle-ergometer exercise until exhaustion. VO2max, blood lactate, urinary proteins and urinary creatinine were analysed to evaluate the exercise performance and proteinuria. IEF and SDS-PAGE analyses were performed to test for differences in electrophoretic behaviour of the endogenous EPO before and after exercise. All subjects showed increased levels of protein/creatinine ratio after performance (8.8±5.2-26.1±14.4). IEF analysis demonstrated an elevation of the relative amount of basic band areas (13.9±11.3-36.4±12.6). Using SDS-PAGE analysis we observed a decrease in rMVs after exercise and no shift in direction of the recombinant human EPO (rhEPO) region (0.543±0.013-0.535±0.012). Following identification criteria of the World Anti Doping Agency (WADA) all samples were negative. The implementation of the SDS-PAGE method represents a good solution to distinguish between results influenced by so called effort urines and results of rhEPO abuse. Thus this method can be used to confirm adverse analytical findings.